A flexible VOCs sensor based on a 3D Mxene framework with a high sensing performance. Issue 37 (12th September 2018) - Yuan, Wenjing; Yang, Kai; Peng, Huifen; Li, Fang; Yin, Fuxing
Abstract : 3D Mxene based gas sensors demonstrated a highly sensitive detection for VOCs in an ultra-wide sensing range at room temperature. Abstract : The development of efficient, low-cost and highly sensitive chemical sensors that can monitor trace amounts of volatile organic compounds (VOCs) has become indispensable for industrial and biomedical applications. Here, we demonstrate a high-performance and flexible VOC sensor based on a 3D Mxene framework (3D-M). The 3D-M was prepared through an effective electrospinning technique coupled with a self-assembly approach. The resulting 3D-M sensor can perform at room temperature, and displays a high sensitivity to extremely low concentrations of VOCs (ppb level) due to its highly interconnected porous structure, which enable the easy access and diffusion of gas molecules. Furthermore, the sensor also exhibits an ultra-wide sensing range (from 50 ppb up to a saturated vapor), fast response and recovery (less than 2 min), and good reversibility and flexibility (no performance decrease for 1000 bending cycles) for various VOCs ( e.g. acetone, methanol and ethanol), demonstrating a great potential for both industrial and biomedical applications.